2017
DOI: 10.1002/2017pa003180
|View full text |Cite
|
Sign up to set email alerts
|

The Northern Gulf of Mexico During OAE2 and the Relationship Between Water Depth and Black Shale Development

Abstract: Despite their name, Oceanic Anoxic Events (OAEs) are not periods of uniform anoxia and black shale deposition in ancient oceans. Shelf environments account for the majority of productivity and organic carbon burial in the modern ocean, and this was likely true in the Cretaceous as well. However, it is unlikely that the mechanisms for such an increase were uniform across all shelf environments. Some, like the northwest margin of Africa, were characterized by strong upwelling, but what might drive enhanced produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 98 publications
0
19
1
Order By: Relevance
“…Seven sites document anoxic conditions before OAE2. They are located in the Southern Central Atlantic and in the Gulf of Mexico (Figure 10; Kuypers et al., 2002; Lowery, Cunningham, et al., 2017; Lowery, Leckie, et al., 2017; Owens et al., 2012; Perez‐Infante et al., 1996; van Helmond, Ruvalcaba Baroni, et al., 2014; Westermann et al., 2014). In particular, previous studies suggested that the anoxic area surrounding the Equatorial Atlantic Gateway was driven by the estuarine circulation established between the Pacific and Central Atlantic (Topper et al., 2011; Trabucho Alexandre et al., 2010) but our results demonstrate that this anoxic area is stable even in the ShallowCAS simulation despite the disappearance of the estuarine circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Seven sites document anoxic conditions before OAE2. They are located in the Southern Central Atlantic and in the Gulf of Mexico (Figure 10; Kuypers et al., 2002; Lowery, Cunningham, et al., 2017; Lowery, Leckie, et al., 2017; Owens et al., 2012; Perez‐Infante et al., 1996; van Helmond, Ruvalcaba Baroni, et al., 2014; Westermann et al., 2014). In particular, previous studies suggested that the anoxic area surrounding the Equatorial Atlantic Gateway was driven by the estuarine circulation established between the Pacific and Central Atlantic (Topper et al., 2011; Trabucho Alexandre et al., 2010) but our results demonstrate that this anoxic area is stable even in the ShallowCAS simulation despite the disappearance of the estuarine circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a compilation of global relative sea level records, constrained by ammonite biostratigraphy and/or δ 13 C chemostratigraphy, reveals coeval sequence boundaries and lowstands underlying OAE2 at many localities, including: the English Chalk (Gale et al, 1993), the Paris Basin (Robaszynski et al, 1998), Germany (Voigt et al, 2006;Richardt et al, 2013), Czech Republic (Uličný et al, 1997), Peru (Navarro-Ramirez et al, 2016, Mexico (Elrick et al, 2009), southern New Mexico (Mack et al, 2016), the northern Gulf of Mexico (Lowery et al, 2017), Jordan (Wendler et al, 2014), Lebanon (Grosheny et al, 2017), Israel (Buchbinder et al, 2000), Egypt (Nagm et al, 2014), and Morocco (Kuhnt et al, 2009). Consistency among these global Upper Cretaceous relative sea level records ties the hiatus in the uppermost Hartland Shale in the WIB to an apparent eustatic lowstand preceding the onset of OAE2, coeval with or just preceding a major pulse of LIP volcanism (Fig.…”
Section: Eustatic Lowstand Preceding Oae2mentioning
confidence: 99%
“…8). Average TOC during OAE2 at Bass River is 1.1 wt % (van Helmond et al, 2014); this is slightly higher than Smith Elementary (0.83 wt %) and Hope Plantation (0.63 wt %) and slightly lower than the next closest published shelf site to the southwest, the Sun Spinks core in Mississippi (1.4 wt %; Lowery et al, 2017). Sequence stratigraphic analysis of Cenomanian-Turonian sediments of the Clubhouse and Bass River formations shows that these sediments represent maximum sea level rise across the boundary on the Atlantic Coastal Plain (Miller et al, 2004;Aleman Gonzalez et al, 2020).…”
Section: Oae2 On the Eastern North American Shelfmentioning
confidence: 76%
“…Estimates of organic carbon mass accumulation rates suggest all three of these inner shelf sites are very similar, ranging from 0.4-0.6 g cm −2 kyr −1 . Average TOC is even higher in the Spinks core (1.4 wt %, or 0.11 g cm −2 kyr −1 ), which represents inner to middle shelf depths during the latter part of OAE2 (Lowery et al, 2017). This suggests the possibility of even higher values on more distal parts of the shelf and highlights the need for a true depth transect (as opposed to four cores from three states) to better understand that variability and better constrain organic carbon burial in this important environment during OAEs.…”
Section: Oae2 On the Eastern North American Shelfmentioning
confidence: 96%